PRODUCT DIVERSITY: KEY TO PURCHASE DECISION AND SATISFACTION AT BINTANG COFFEE AND RESTAURANT, MOROWALI DISTRICT - Riska Nining Lestari; Moh. Zeylo Auriza; Zakiyah Zahara (Electronic Journal of Education, Social Economics and Technology, 2025)
This study aims to determine the effect of product diversity on customer satisfaction through purchasing decisions at Bintang Coffee and Restaurant in Morowali Regency. This study uses a quantitative approach with Structural Equation Modeling (SEM) analysis techniques based on SmartPLS. The research sample consisted of 150 respondents. The results of the study indicate that product diversity has a significant effect on purchasing decisions and customer satisfaction, and purchasing decisions act as a mediator in the relationship. These findings reinforce the importance of managing product variety to improve customer satisfaction in the local restaurant sector.